You ‘again’: an acquisition study on its restitutive reading with goal-PPs - Xu, Ting; Snyder, William; Christie, Stella (Glossa (London), 2024)
Availability of restitutive ‘again’ varies both cross-linguistically and language-internally. This creates an acquisition puzzle: For each change-of-state predicate, how do children know if a restitutive reading is possible? In child-directed English, unambiguously restitutive uses of ‘again’ with a “goal-PP” structure (e.g., ‘walk to the village’) are exceedingly rare. Nonetheless, comprehension tasks with goal-PPs show that preschoolers already know the reading is available. Here we show that the same pattern holds for Mandarin you (roughly, ‘again’): extremely little direct, unambiguous evidence for the restitutive reading with goal-PPs, but preschoolers already know it is possible. This pattern is all the more remarkable for Mandarin because you is both preverbal and polysemous, making it less transparent how the restitutive reading is obtained. We propose that our findings fit neatly in a structural approach, where restitutive readings involve attaching ‘again’ to a VP-internal result phrase: The child can deduce the availability of restitutive you if they have acquired both the property allowing repetition-denoting you to semantically compose with a sub-constituent of the VP, and the structural properties of Mandarin goal-PPs that make a restitutive reading possible.